GAME EDUKASI PEMBELAJARAN MATEMATIKA PERSAMAAN LINIER BERBASIS ANDROID - virginiawan, virginiawan; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2020)
Research this educational gameaims to make mathematics teaching material in the form of educational games on linear equality material for grade VII junior high school / MTs, as well as knowing the quality of teaching materials seen from the effectiveness and practicality of the educational game. Educational game research is carried out based on the 4D (Four-D) model, but in this study it was carried out to stage three, namely the define, design, and development stages. This educational game is supported with HTML5-based software extract with a 2D platform developed by Scirra. While the components - components in making educational games are opening splash screen (opening), menu screen (menu display), music (music), sound effects (sound effects), obsctacle (obstacles), levels (levels), adversaries (opponents / enemies) ), player (player), and scene (scene). Responses to student learning achievement test questions to measure the effectiveness of educational games and teacher and student questionnaire responses to measure the practicality of the educational game. Educational game trials were conducted at MTs Teluk Sasah in grades VII and VIII. The results of this study are in the form of an android-based mathematical linear learning educational game. Based on the results of the study it was found that the educational game that was made effective and practical.